Surface modification of doxorubicin-loaded nanoparticles based on polydopamine with pH-sensitive property for tumor targeting therapy - Dongdong Bi; Lei Zhao; Runqi Yu; Haowen Li; Yifei Guo; Xiangtao Wang; Meihua Han (Taylor & Francis Group, 2018)
One major challenge of current surface modification of nanoparticles is the demand for chemical reactive polymeric layers, such modification is always complicated, inefficient, and may lead the polymer lose the ability to encapsulate drug. To overcome this limitation, we adopted a pH-sensitive platform using polydopamine (PDA) as a way of functionalizing nanoparticles (NPs) surfaces. All this method needed to be just a brief incubation in weak alkaline solution of dopamine, which was simple and applicable to a variety of polymer carriers regardless of their chemical reactivity. We successfully conjugated the doxorubicin (DOX)-PDA-poly (lactic-co-glycolic acid) (PLGA) NPs with two typical surface modifiers: folate (FA) and a peptide (Arg-Gly-Asp, RGD). The DOX-PDA-FA-NPs and DOX-PDA-RGD-NPs (targeting nanoparticles) were characterized by particle size, zeta potential, and surface morphology. They were quite stable in various physiological solutions and exhibited pH-sensitive property in drug release. Compared to DOX-NPs, the targeting nanoparticles possessed an excellent targeting ability against HeLa cells. In addition, the in vivo study demonstrated that targeting nanoparticles achieved a tumor inhibition rate over 70%, meanwhile prominently decreased the side effects of DOX and improve drug distribution in tumors. Our studies indicated that the DOX-PLGA-NPs modified with PDA and various functional ligands are promising nanocarriers for targeting tumor therapy.